Herpes Simplex Virus Type 1 2-Kilobase Latency-Associated Transcript Intron Associates with Ribosomal Proteins and Splicing Factors - Ahmed, Maryam (American Society for Microbiology, 2001)
During latency of herpes simplex virus type 1 in sensory neurons, the transcription of viral genes is restricted to the latency-associated transcripts (LATs). The stable 2-kb LAT intron has been characterized previously and has been shown to accumulate to high levels in the nuclei of infected neurons. However, in productively infected tissue culture cells, this unique intron is also found in the cytoplasm. Although deletion mutant analysis has suggested that the region of the gene from which the intron is spliced plays a role in maintenance of latency or in reactivation from latency, no well-defined function has been ascribed specifically to the 2-kb LAT intron. Nevertheless, previous work has shown that it associates with 50S particles in the cytoplasm of acutely infected cells. Our studies tested the ability of the 2-kb LAT to dissociate from cytoplasmic protein complexes under various salt conditions. Results indicated that this association, which had been speculated to be mRNA-like, is actually more similar to the affinity of rRNAs for translational complexes. Furthermore, by immunoprecipitation analysis, we demonstrate that the 2-kb LAT associates with ribosomal as well as with splicing complexes in infected cells. Our results suggest that the 2-kb LAT is processed similarly to mRNAs in the nuclei of infected cells. However, in the cytoplasm, the 2-kb LAT may play a structural role in the ribosomal complex, similar to that of the cellular rRNAs, and therefore affect the functioning of the translational machinery.